The role of senescence-associated secretory phenotype (SASP) in cellular senescene - Filda Vionita Irene de Lima; Novi Silvia Hardiany (Acta Biochimica Indonesiana, 2021)
Cellular senescence is one of the defense mechanisms of cells against oncogenic signals by permanently stopping the proliferation of the cell. Senescence cells show a similar characteristic, one of them is senescence-associated secretory phenotype (SASP). SASPs secrete various components, divided according to the type of molecule secreted and based on their mechanism of action against target cells. The main components of SASP are pro-inflammatory mediators. SASP performs dual and contradictory roles, which concurrently provides beneficial effects such as tumor suppression due to the termination of proliferation, recruitment of immune cells, and tissue repair. On the other hand, SASP produces detrimental effects on cells undergoing the senescence process as well as cells in the surrounding environment by increasing tumorigenesis. This review article explains the various components of the SASP, the role of SASP in the inflammatory process, tumor suppression, and tumorigenesis.